Properties of CMAS glass from desert sand. Issue 3 (April 2015) - Bansal, Narottam P.; Choi, Sung R.
Abstract: X-ray diffraction analysis of as-received desert sand from a Middle East country showed the presence of quartz (SiO2 ), calcite (CaCO3 ), gypsum (CaSO4 .2H2 O), NaAlSi3 O8, Mg2 (Al3.9 Si5.1 O18 ) and Mg3 Al2 (SiO4 )3 phases. A batch of as-received desert sand was melted into calcium magnesium aluminosilicate (CMAS) glass at ~1500 °C. From inductively coupled plasma-atomic emission spectrometry, chemical composition of the CMAS glass was analyzed to be 27.8CaO-4MgO-5Al2 O3 -61.6SiO2 -0.6Fe2 O3 -1K2 O (mole %). Various physical, thermal, and mechanical properties of the glass have been evaluated. Bulk density of CMAS glass was 2.69 g/cm 3, Young׳s modulus 92 GPa, Shear modulus 36 GPa, Poisson׳s ratio 0.28, dilatometric glass transition temperature (Tg ) 706 °C, softening point (Td ) 764 °C, Vickers microhardness 6.3±0.4 GPa, indentation fracture toughness 0.75±0.15 MPa.m 1/2, and coefficient of thermal expansion (CTE) 9.8×10 −6 /°C in the temperature range 25 to 700 °C. Temperature dependence of viscosity has also been estimated from various reference points of the CMAS glass using the Vogel-Fulcher-Tamman (VFT) equation as well as from the glass composition. The glass remained amorphous after heat treating at 850 °C for 10 h but crystallized into CaSiO3 and Ca2 Mg0.5 AlSi1.5 O7 phases at 900 °C or higher temperatures. Crystallization kinetics of the CMAS glass has also been investigated by differential thermal analysis (DTA).